Epidemiological Scenario of Dengue in Brazil. (30th August 2015) - Fares, Rafaelle C. G.; Souza, Katia P. R.; Añez, Germán; Rios, Maria
Abstract : Dengue is the most important reemerging mosquito-borne viral disease worldwide. It is caused by any of four Dengue virus types or serotypes (DENV-1 to DENV-4) and is transmitted by mosquitoes from the genus Aedes . Ecological changes have favored the geographic expansion of the vector and, since the dengue pandemic in the Asian and Pacific regions, the infection became widely distributed worldwide, reaching Brazil in 1845. The incidence of dengue in Brazil has been frequently high, and the number of cases in the country has at some point in time represented up to 60% of the dengue reported cases worldwide. This review addresses vector distribution, dengue outbreaks, circulating serotypes and genotypes, and prevention approaches being utilized in Brazil.